The Four Gods Figurines as Tomb Guardians: Their Function, Circulation, and Disappearance in Tang China (618–907 AD) - Yang, Lok Man (J.B. Metzler, 2023)
Introduction -- Four Gods as a Dual Symbol: Apotropaic and Political Significance -- Re-examining the Establishment of the Tomb Guardian Beasts, and the Iconography of the Four Gods -- Meaning and Function of the Assemblages of the Supernatural Figurines -- Use and Circulation of Four Gods -- Disappearance of Four Gods and New Perceptions Related to Apotropaic Practices in Tombs -- Conclusion.
Gesehen am 05.01.2024
Keywords: Hochschulschrift; Götterstatue; Grabplastik; Tangdynastie